Flexural performance of CFRP strengthened RC beams with different degrees of strengthening schemes - Norsuzailina, Sutan; Ehsan, Ahmed; Habibur Rahman, Sobuz (Academic Journals, 2011)
Externally bonded carbon fiber reinforced polymer (CFRP) composite laminates have been successfully applied to reinforced concrete (RC) beams and other structural elements for the purpose of increase load carrying capacity of such elements. This paper presents the experimental results on the flexural strengthening of reinforced concrete beams by CFRP laminates attached to the tensile soffit of the beams by epoxy adhesive. A total of six reinforced concrete beams having different degrees of strengthening scheme were tested to failure under transverse bending over an effective span length of 1900 mm. The increase of ultimate strength provided by the bonded carbon fiber was assessed by varying the layers of composite laminates. The results indicate that the flexural strength of beams was significantly improved as the layers of laminate increased. No de-lamination of the superimposed CFRP plates was observed from the test. However, de-bonding of CFRP laminates from concrete surface was observed for the case of multi-layer strengthening of beam. It is concluded that the attachment of CFRP laminates with edge strip plates has substantially influenced the performance of CFRP strengthened beams. The paper also highlighted the beams failure modes due to the different level of strengthening scheme.